Literary reading as an experience for hospitalized children in the oncology ward of the Hospital Universitario de Santander (HUS) - Gómez Rodríguez, Jhonatan Fabián; Gómez Rodríguez, Alejandro; Ojeda Avellaneda, Ana Cecilia (Rastros Rostros, 2021)
Traditionally, the reading activities and children’s literature have been present in the school context. But in there their function is limited to teaching pedagogically or morally: to read for learn curricular contents or moral lessons of good behavior. In this situation, it was necessary to explore other spaces - the hospital, in this case - where the reading and children’s literature be meaningful experiences, far away from the traditional teaching functions. What impact could literary reading have in hospital populations and hospital contexts? Objective: To guide literary reading as a significant experience in children-patients of the Hospital Universitario de Santander (HUS). Methodology: Case study, with a qualitative approach, of 3 child-patients with 4-5 years old, hospitalized at the Hospital Universitario de Santander (HUS). During a month, the participants received 4 face-to-face reading classes with books chosen according to the needs of each child. The impact was evaluated through mood scales (before and after reading), research field notes, and interviews with parents and hospital staff. Results: The reading classes had a positive impact: in the after reading moment of each session, the initial negative moods of patients-participants decreased (restlessness, sadness, worry, annoyance), while their positive moods (joy, tranquility, satisfaction) increased. Conclusions: Literary reading classes in hospital contexts not only work as a leisure activity, but also as a strategy for psycho-emotional support in children-patients while the process of illness and hospitalization. Additionally, the present of parents during the reading process is essential to achieve a better acceptance of reading by children-patients.